Pretreatment and enzymatic process modification strategies to improve efficiency of sugar production from sugarcane bagasse - Pal, Siddhartha; Joy, Shereena; Trimukhe, Kalpana D.; Kumbhar, Pramod S.; Varma, Anjani J.; Padmanabhan, Sasisanker (3 Biotech, 2016)
Pretreatment and enzymatic hydrolysis play a critical role in the economic production of sugars and fuels from lignocellulosic biomass. In this study, we evaluated diverse pilot-scale pretreatments and different post-pretreatment strategies for the production of fermentable sugars from sugarcane bagasse. For the pretreatment of bagasse at pilot-scale level, steam explosion without catalyst and combination of sulfuric and oxalic acids at low and high loadings were used. Subsequently, to enhance the efficiency of enzymatic hydrolysis of the pretreated bagasse, three different post-pretreatment process schemes were investigated. In the first scheme (Scheme 1), enzymatic hydrolysis was conducted on the whole pretreated slurry, without treatments such as washing or solid-liquid separation. In the second scheme (Scheme 2), the pretreated slurry was first pressure filtered to yield a solid and liquid phase. Following filtration, the separated liquid phase was remixed with the solid wet cake to generate slurry, which was then subsequently used for enzymatic hydrolysis. In the third scheme (Scheme 3), the pretreated slurry was washed with more water and filtered to obtain a solid and liquid phase, in which only the former was subjected to enzymatic hydrolysis. A 10 % higher enzymatic conversion was obtained in Scheme 2 than Scheme 1, while Scheme 3 resulted in only a 5-7 % increase due to additional washing unit operation and solid-liquid separation. Dynamic light scattering experiments conducted on post-pretreated bagasse indicate decrease of particle size due to solid-liquid separation involving pressure filtration provided increased the yield of C6 sugars. It is anticipated that different process modification methods used in this study before the enzymatic hydrolysis step can make the overall cellulosic ethanol process effective and possibly cost effective.
Keywords: Dilute acid treatment; High-solid enzymatic hydrolysis; Pilot-scale pretreatment; Pressure filtration; Solid-liquid separation

Facile synthesis of unique cellulose triacetate based flexible and high performance gel polymer electrolyte for lithium ion batteries - Nirmale, Trupti C.; Karbhal, Indrapal; Kalubarme, Ramchandra S.; Shelke, Manjusha V.; Varma, Anjani J.; Kale, Bharat B. (ACS Applied Materials & Interfaces, 2017)
Lithium ion batteries (LIBs) with polymer based electrolytes have attracted enormous attention due to the possibility of fabricating intrinsically safer and flexible devices. However, economical and eco-friendly sustainable technology is an oncoming challenge to fulfill the ever increasing demand. To circumvent this issue, we have developed a gel polymer electrolyte (GPE) based on renewable polymers like cellulose triacetate and poly (polyethylene glycol methacrylate) p(PEGMA) using a photo polymerization technique. Cellulose triacetate offers good mechanical strength with improved ionic conductivity, owing to its ether and carbonyl functional groups. It is observed that the presence of an open network has a critical impact on lithium ion transport. At room temperature, GPE PC exhibits an optimal ionic conductivity of 1.8 x 10(-3) S cm(-1) and transference number of 0.7. Interestingly, it affords an excellent electrochemical stability window up to 5.0 V vs Li/Li+. GPE PC shows a discharge capacity of 164 mAhg(-1) after the first cycle when evaluated in a Li/GPE/LiFePO4 cell at 0.5 C-rate. Interfacial compatibility of GPE PC with lithium metal improves the overall cycling performance. This system provides a guiding principle toward a future renewable and flexible electrolyte design for flexible LIBs (FLIBs).

Pilot-scale pretreatments of sugarcane bagasse with steam explosion and mineral acid, organic acid, and mixed acids: synergies, enzymatic hydrolysis efficiencies, and structure-morphology correlations - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod S.; Trimukhe, Kalpana D.; Gupta, Rishi; Kuhad, Ramesh Chander; Varma, Anjani J.; Shankar, Sasi (Biomass Conversion and Biorefinery, 2017)
In lignocellulosic (LC) ethanol processes, to facilitate enzymatic hydrolysis of cellulose, a physical chemical pretreatment is vital. In this study, we explored a single as well as a two-step physical-chemical pretreatment involving steam and mixed acid on unwashed sugarcane bagasse at pilot-scale level in a continuous horizontal reactor. To serve as a large-scale model, pretreatments were carried out at high solid levels of 18–20 % w/w. For the pretreatment, partial replacement of corrosive sulfuric acid with a milder acid-like oxalic acid was explored to derive possible advantages and synergies accruing by using a mixture of mineral acid and organic acid. The results of this work showed that first-step pretreatment carried out by the mixing of sulfuric acid (1.5 % w/w) and oxalic acid (1.5 % w/w) at 150 °C followed by a second-step steam explosion pretreatment at 180 °C gave significant synergies and advantages over other variants of pretreatments investigated, such as lower inhibitor levels and lower reaction severity. On post-pretreated bagasse, this study conducted comparative enzymatic hydrolysis study using a simple lab enzyme and a robust commercial enzyme. It was found that the addition of Tween 80 to the lab enzyme improved its performance to match the performance of the commercial enzyme. Scanning electron microscopy (SEM) studies were further carried out to correlate the morphology of pretreated samples with efficiency of enzyme hydrolysis. Besides morphological study, Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl ratio for all pretreatments, indicating lower levels of pseudo-lignins, which is beneficial for improved enzyme hydrolysis.

Review on cellulose and lignin based binders and electrodes: Small steps towards a sustainable lithium ion battery - Nirmale, Trupti C.; Kale, Bharat B.; Varma, Anjani J. (International Journal of Biological Macromolecules, 2017)
Lithium ion batteries (LIB) are the most promising energy storage systems for portable electronics and future electric or hybrid-electric vehicles. However making them safer, cost effective and environment friendly is the key challenge. In this regard, replacing petro-derived materials by introducing renewable biomass derived cellulose derivatives and lignin based materials into the battery system is a promising approach for the development of green materials for LIB. These biomaterials introduce sustainability as well as improved safety in the final disposal of LIB batteries. In this review we introduce LIB materials technology in brief and recent developments in electrodes and binders based on cellulose and their derivatives and lignin for lithium ion batteries. (C) 2017 Elsevier B.V. All rights reserved.